Creep enhancement and sliding in a temperate, hard-bedded alpine glacier - J.-P. Roldán-Blasco; A. Gilbert; L. Piard; F. Gimbert; C. Vincent; O. Gagliardini; A. Togaibekov; A. Togaibekov; A. Walpersdorf; N. Maier (The Cryosphere)
Glacier internal deformation is usually described by Glen's flow law using two material parameters: the creep factor (A) and the flow law exponent (n). However, the values of these parameters and their spatial and temporal variability are rather uncertain due to the difficulty in quantifying internal strain and stress fields at natural scales. In this study, we combine 1-year-long continuous measurements of borehole inclinometry and surface velocity with three-dimensional full-Stokes ice flow modeling to infer ice rheologies and sliding velocities for the ablation zone of the Argentière Glacier, a temperate glacier in the French Alps. We demonstrate that the observed deformation rate profile has limited sensitivity to the flow law exponent (n) and instead mainly reflects an increase in the creep factor (A) with depth, with A departing from its surface value by up to a factor of 2.5 below 160 m depth. We interpret this creep factor enhancement as an effect of increasing interstitial water content with depth (from 0 % to 1.3 %), which results in an average value of A=148 MPa−3 a−1. We further observe that internal ice deformation exhibits seasonal variability similar to that concerning surface velocity, indicating that the local basal sliding velocity exhibits no significant seasonal variation. We suggest that these changes in deformation rate are due to variations in the stress field, driven by contrasting changes in subglacial hydrology conditions between the sides and center of the glacier. Our study provides further evidence that borehole inclinometry, combined with full-Stokes flow modeling, allows for the constraining of both ice rheology and basal friction at scales that cannot be inferred from surface velocity measurements alone.